Pengaruh Media Sosial Instagram Terhadap Perilaku Masyarakat - Nunung Nurhasanah; Ageng Saepudin Kanda S (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The development of social media from time to time continues to be in the spotlight for domestic and foreign audiences, this is in line with the times which continue to accelerate due to the creation of new things, including social media. The development of social media continues to be important in human society for the development of change from before and becomes the public's own assumptions. Social media is currently controlled by teenagers who follow the latest trends regarding social media and one of the social media which is currently in the spotlight and is popular with many people, especially teenagers, is the social media Instagram which is being consumed by everyone, especially by teenagers. teenage students who keep up with the times and the development of Instagram which has entered all parts of the world, including Indonesia.Currently, Instagram users have reached 104.8 million+, with this value Indonesia is the fourth most used Instagram in the world. The large number of Instagram users is not only among women or teenagers, but based on gender, men dominate global Instagram users aged 18 years and over with a proportion of 50.3%, while women are 49.7%. As for Instagram became the social media application with the fourth most users in the world as of October 2023 according to We Are Social. Its position is below Facebook, YouTube and WhatsApp.Among the people, Instagram is no longer foreign, now more people use Instagram to get the latest and most up-to-date information. Not only that, people can also get entertainment from Instagram